Bioethanol and Biodiesel from Second Generation Feedstocks: A Promising Solution to Energy Shortages in Pakistan: Bioethanol and Biodiesel from Second Generation Feedstocks - Khichi, Ali Hassnain Khan (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2017)
Pakistan is facing acute shortage of energy which, in turn, is adversely affecting its economic growth besides discomfort to its vast population. Concurrently, the country is faced with gigantic challenges of rapid increase in population, increased number of motor vehicles on the roads, and urbanization; these adverse developments are leading to ever increasing demand for energy. Having inadequate indigenous energy resources, Pakistan relies heavily on expensive oil imports in the face of foreign exchange scarcity. Thus, the import bill for oil is a big drain on its financial resources. Therefore, alternate sources of energy are need of the hour. Biofuels offer a number of benefits: environmental, economic and geo-political benefits. This article reports an in-depth secondary research with the objective of addressing energy shortages by utilizing an alternate means. The issues related to use of ethanol and biodiesel are energy sources are discussed; and it appears that use of biofuels in Pakistan can help in reducing energy shortage to some extent.